Intrahepatic Biliary Cystadenoma With Colonic Adenomatous Polyps in a Patient With Chronic Hepatitis B: A Case Report and Literature Review - Tang, Yan; Wang, Chenyu; Fu, Shunjun; Li, Ting; He, Guolin (Frontiers in Medicine, 2021)
Background: Biliary cystadenomas are rare cystic tumors of the bile duct system that are mostly benign but also have the possibility of malignant transformation. Biliary cystadenomas mostly occur in the intrahepatic bile ducts and are more common in middle-aged women. Due to non-specific radiology, preoperative diagnosis is difficult and is usually performed by postoperative pathology. Complete resection is the best treatment option, and the postoperative prognosis is good. Case Description: This study reports a case of a patient with biliary cystadenoma who was diagnosed with simultaneous chronic hepatitis B and colon (hepatic flexure) adenomatous polyps. The patient presented to the doctor because of abdominal pain, and a blood test showed hepatitis B. Computed tomography revealed both right liver and colonic lesions. Colonoscopy revealed polyps, and the postoperative pathological diagnosis was adenomatous polyps. Laparoscopic resection of the right liver tumor was performed, and it was diagnosed as hepatobiliary cystadenoma by postoperative pathological analysis combined with immunohistochemistry. Conclusion: In patients with chronic hepatitis, the shape of biliary cystadenoma may not be very typical, and it is necessary to combine this with immunohistochemistry for diagnosis. When multiple lesions are detected in the painful area, the diagnosis of each lesion and its treatment sequence are worthy of consideration. Under normal circumstances, the prognosis of biliary cystadenoma is good; however, in patients with chronic hepatitis B, more cases need to be observed for verification.